2008
DOI: 10.1111/j.1365-2435.2008.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolite production facilitates establishment of rhizobacteria by reducing both protozoan predation and the competitive effects of indigenous bacteria

Abstract: Summary 1.Rhizosphere bacteria live in close contact to plant roots feeding on root exudates and rhizodeposits. By producing toxic exoproducts rhizobacteria may inhibit plant pathogens thereby functioning as biocontrol agents and increasing plant fitness. However, the evolutionary basis why rhizobacteria protect plants is little understood. To persist toxin production needs to improve the competitiveness of the bacteria themselves. 2. We investigated the importance of secondary metabolite production for the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 32 publications
2
76
0
2
Order By: Relevance
“…The strong and highly reproducible changes in the gacA-banding pattern further revealed a major shift in this master gene controlling antibiotics production of pseudomonads (De Souza et al, 2003). We suggest that pseudomonads quickly upregulated secondary metabolite production in response to protozoan predators, which is in accordance with Jousset et al (2006) who demonstrated that antibiotics of P. fluorescens are of particular toxicity to protozoa; and that antibiotic-producing P. fluorescens disproportionally benefit from protozoan predation when their bacterial competitors are consumed and nutrients excreted by the protozoan predators (Jousset et al, 2008).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The strong and highly reproducible changes in the gacA-banding pattern further revealed a major shift in this master gene controlling antibiotics production of pseudomonads (De Souza et al, 2003). We suggest that pseudomonads quickly upregulated secondary metabolite production in response to protozoan predators, which is in accordance with Jousset et al (2006) who demonstrated that antibiotics of P. fluorescens are of particular toxicity to protozoa; and that antibiotic-producing P. fluorescens disproportionally benefit from protozoan predation when their bacterial competitors are consumed and nutrients excreted by the protozoan predators (Jousset et al, 2008).…”
Section: Discussionsupporting
confidence: 67%
“…Soil amoebae have been shown to graze preferentially on Gram-negative bacteria (Foster and Dormaar, 1991;Andersen and Winding, 2004). Not surprising, the gacA regulated antibiotic production of pseudomonads has been found to play also a significant role in bacterial defence against protozoan predators (Jousset et al, 2006(Jousset et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Data showing a role for phenazine antibiotics in microbial competitiveness (Mazzola et al 1992) are consistent with our hypothesis that antibiotic production does not depend on whether plants benefit. This conclusion is emphasized by more recent results, including bacteriocin-mediated antagonism among G. diazotrophicus strains (Munoz-Rojas et al 2005) and a role for antibiotics in defense against predation by protozoa and competition with other bacteria (Jousset et al 2006(Jousset et al , 2008.…”
Section: Antimicrobial Mutualismsmentioning
confidence: 85%
“…Fluorescent pseudomonads are ubiquitous rhizosphere bacteria, and many species produce toxic exoproducts that increase their resistance to microfaunal predators and improve their competitiveness against other bacteria (Jousset et al, 2008). These toxins often inhibit plant pathogens, making pseudomonads as potent biological control agents in agricultural systems (Haas and Defago, 2005).…”
Section: Introductionmentioning
confidence: 99%